Reliability-based multiobjective optimisation of vehicle bumper structure holes for the pedestrian flexible legform impact. Issue 3 (3rd May 2016) - Lv, Xiaojiang; Huang, Xiaodong; Gu, Xianguang; Liu, Weiguo; Li, Guangyao
ABSTRACT: Vehicle bumper structure can effectively protect the pedestrian lower extremity from severe injury in vehicle–pedestrian collision; thus, its design signifies a key issue in automobile engineering. This study considers the manual prototype production process tolerance of six design variables describing two holes in the bumper structure. To ensure a high safety rating in the European New Car Assessment Programme (Euro-NCAP) rating system, the anterior cruciate ligament (ACL) elongation and the tibia bending moment of T3 are taken as objectives, while the posterior cruciate ligament (PCL) elongation, the medial collateral ligament (MCL) elongation, the tibia bending moment of T1, the tibia bending moment of T2 and the tibia bending moment of T4 as constrains in the optimisation process. By combining the non-dominated sorting genetic algorithm II (NSGA-II) and the Monte Carlo simulation (MCS) method, the proposed optimisation methodology provides an analytic and systematic tool for optimising the multiple objective functions and evaluating the probabilistic constraint functions simultaneously. The Pareto fronts from the deterministic, 90% and 99% reliability design are compared and analysed. Compared with the initial design, the 99% reliability design result shows that the pedestrian lower extremity injury indicators of T3 and ACL can be decreased by 10.09% and 26.25%, respectively.